as a society are we protecting children? - Rincón Balaguera, Monica Paola (Universidad Pedagógica y Tecnológica de Colombia, 2018)
It is intended to carry out an analysis, from the vulnerability and lack of protection of the victims of pedophilia and in a more tangential way on the inadequate treatment that is provided to the perpetrators. To do this, several perspectives are taken into account, especially the legal one. The phenomenon was studied through a qualitative method, where documents and observation were the data of interest. The information that was collected and served as support, was extracted from contexts where situations of pedophilia have been experienced. In Colombia, the problem of the sexual abuse of minors has taken on unexpected dimensions, making it necessary to rethink the criminal policy and all those policies that are related to the prevention of abuse; most statistics indicate that this is one of the most serious ways of damaging the physical, moral and psychological integrity of the victims. Pedophilia, considered a crime, punishable by penalties that does not comply with its fines and does not provide protection to minors; allows to make a reproach to the ineffectiveness and insufficiency of the norm and the criminal policy, in the face of this disorder, in a society where the real and effective protection of the rights of children has become a necessity.